The British Art Show 4 :. - Cork, Richard; Hughes, Henry Meyric; Lawson, Thomas; Lewis, Vicki; Malbert, Roger (London : Hayward Gallery, 1995)
Baseman, Jordan ; Borland, Christine ; Collishaw, Mat ; Dean, Tacita ; Floyer, Ceal ; Frankland, John ; Gallaccio, Anya ; Gordon, Douglas ; Hirst, Damien ; Hume, Gary ; Kaur, Permindar ; McQueen, Steve ; Nogueira, Lucia ; Ofili, Chris ; Roberts, Julie ; Smith, Bridget ; Starr, Georgina ; Stewart, Kerry ; Taylor, Marcus ; Taylor-Wood, Sam ; Wallinger, Mark ; Wearing, Gillian ; Wiltshire, Hermione ; Wilson, Jane & Louise ; Yass, Catherine
+ bijlage
biografie
Engels
National Touring Exhibitions, Manchester : Upper Campfield Market, Castlefield, Castlefield Gallery, Chinese Arts Centre, City Art Galleries, Cornerhouse, Metropolitan Galleries, Whitworth Art Gallery, 12 November 1995 - 4 February 1996 ; Edinburgh : City Art Centre, Collective Gallery, Fruitmarket Gallery, Royal Botanic Garden, Scottish National Gallery of Modern Art, Stills Gallery, Talbot Rice Gallery, Edinburgh, 24 February - 28 April 1996 ; Cardiff : Chapter Arts Centre, Ffotogallery, National Museum of Wales, Oriel Gallery (in collaboration with St. David's Hall and Cardiff Bay Art Trust)
boek
Keywords: Groot-Brittannië